2016
DOI: 10.1080/15384047.2016.1210732
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis: A new way of dying?

Abstract: This review embarks upon a cell death journey from the discovery of apoptosis and necrosis through to the coalescence of these: necroptosis. The mechanisms of 2 emerging necrotic cell death pathways, pyroptosis and ferroptosis, will be explored before delving into apoptotic and necroptotic signaling cascades, highlighting the complex interplay between molecular players. The involvement of the ripoptosome, interferon signaling and DNA damage in necroptosis will be discussed briefly. The major focus is on necrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 120 publications
0
62
0
4
Order By: Relevance
“…However, it was recently shown that activation of PARP1 in the presence of high levels of DNA damage directly suppresses glycolysis via inhibition of hexokinase 1, leading to cell death [55]. Another form of cell death termed necroptosis is also activated in cells harboring DNA damage (for a review see [56]). Cellular debris emanating from dead or dying cells is normally cleared by phagocytes and macrophages (for a review see [57].…”
Section: Mechanisms Associated With Defective Dna Repair and Slementioning
confidence: 99%
“…However, it was recently shown that activation of PARP1 in the presence of high levels of DNA damage directly suppresses glycolysis via inhibition of hexokinase 1, leading to cell death [55]. Another form of cell death termed necroptosis is also activated in cells harboring DNA damage (for a review see [56]). Cellular debris emanating from dead or dying cells is normally cleared by phagocytes and macrophages (for a review see [57].…”
Section: Mechanisms Associated With Defective Dna Repair and Slementioning
confidence: 99%
“…However, apoptosis is a programmed cell death modality, generally triggered by physiological processes, whereas necrosis is an uncontrolled and accidental cell death modality triggered by pathological processes. Necroptosis, a novel cell death modality, involves the loss of membrane integrity and occurs by a programmable mechanism with a characteristic necrotic cell death phenotype [10-13]. Necroptosis is initiated by the activation of receptor interacting protein (RIP) kinases and mixed-lineage kinase domain-like protein (MLKL).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the relatively "clean" death associated with apoptosis, cells that are necroptotic release their intracellular contents en masse into the surrounding milieu, due to the plasma membrane rupture mediated by MLKL. The highly inflammatory response that occurs following intracellular content release into the microenvironment (necroinflammation) after necroptosis may be a consequence of several of these intracellular components, since the cytosol can contain various pro-inflammatory cytokines (induced by NF-κB and p38), as well as constitutive damageassociated molecular patterns (DAMPs) [45][46][47].…”
Section: Apoptosis Vs Necroptosismentioning
confidence: 99%
“…Pro-inflammatory cytokines and chemokines are released from necroptotic corpses. Cytokines such as TNF can lead to further activation of cell death pathways including necroptosis in surrounding cells [46,47]. Moreover, these pro-inflammatory mediators can directly influence cells of the immune system such as macrophages, leading to further inflammatory output in what could be described as a positive feedback loop for inflammation.…”
Section: Damping Out Immune Silencementioning
confidence: 99%